An Integrated Modeling Approach for Analyzing the Deformation Style of Active Volcanoes: Somma‐Vesuvius Case Study. Issue 1 (10th January 2022) - De Matteo, Ada; Massa, Bruno; Castaldo, Raffaele; D'Auria, Luca; James, Mike R.; Lane, Stephen J.; Pepe, Susi; Tizzani, Pietro
Abstract: The deformation style of active volcanoes can provide insight into the structural evolution of their edifices, volcanic activity and associated hazards. The Somma‐Vesuvius volcano is considered one of the most dangerous on the planet due to its proximity to the megacity of Naples (Southern Italy). Thus, understanding its deformation style and corresponding long‐term structural evolution are critical aspects for risk reduction. Although a large amount of data has already been collected about Somma‐Vesuvius, the deformation style affecting its volcanic edifice is still debated. Therefore, we devised an integrated approach to clarify the current state of deformation of this volcano. In particular, we combined analog experiments and finite element (FE) modeling to constrain the current deformation style affecting Somma‐Vesuvius and determine the physical parameters controlling its structural evolution. The analog models were built at a scale of 1:100, 000 using sand mixtures (brittle analog) and polydimethylsiloxane (ductile analog). The FE models were implemented by considering a three‐dimensional time‐dependent fluid‐dynamic approach performed at both the analog model scale (1:100, 000) and actual volcano scale (1:1). We obtained an FE model and a corresponding analog one that faithfully reproduced the observed deformation velocity patterns revealed by differential interferometric synthetic aperture radar (DInSAR) and GPS measurements at Somma‐Vesuvius. Overall, our results support the hypothesis that a combined gravitational spreading‐sagging process governs the deformation style of Somma‐Vesuvius. Plain Language Summary: Volcanic edifices of sufficient mass are capable of deforming substrata under their own weight; this deformation in turn can deform the volcanic edifices themselves. Identifying the deformation style characterizing a volcanic edifice is useful when considering the evolution of its volcanic activity. Vesuvius is considered one of the most dangerous volcanoes on the planet due to its proximity to the megacity of Naples (Southern Italy). Thus, understanding its deformation style and corresponding structural evolution are critical aspects for risk reduction. In order to analyze the deformation process of Vesuvius we used two different modeling techniques: analog modeling and Finite Element numerical modeling. The analog modeling approach allows us to reproduce real processes by using scaled models and media considered analog to natural materials under a physical point of view. The combination of analog and numerical modeling allowed us to constrain the current deformation style affecting Somma‐Vesuvius and to determine the physical parameters controlling its structural evolution. Finally, we compared our results with the observed deformation velocity patterns revealed by Differential Interferometric Synthetic Aperture Radar and GPS measurements at Vesuvius. Overall, the results support the hypothesis that a combined gravitational spreading‐sagging process governs the deformation style of Somma‐Vesuvius. Key Points: Analog and numerical modeling highlighted an active spreading‐sagging process at the Somma‐Vesuvius volcano A comparison of models with differential interferometric synthetic aperture radar (DInSAR) deformation data validated the modeling procedures The spreading process affecting the Vesuvius volcano allowed inferring about the near‐future eruption style